Case Report: An Internal Mammary Rhabdomyosarcoma After Mastectomy and Systemic and Radiation Therapy in a Patient With Breast Cancer - Wang, Dan-Qiong; Zhang, Jing-Yi; Li, Jing; Ying, Jian-Ming; Wang, Xiang; Fan, Ying; Wang, Shu-Lian (Frontiers in Oncology, 2021)
Post-radiation soft tissue sarcomas (PRSTSs) are rare secondary malignancies. In this report, we describe the clinical presentation of a 52-year-old woman who underwent postmastectomy radiation therapy (PMRT) for left-sided breast cancer 2.7 years ago and presented with a left internal mammary mass and left interpectoral nodule on computed tomography. On further evaluation, she was diagnosed with internal mammary rhabdomyosarcoma and interpectoral nodal breast cancer relapse, and was treated with chemotherapy, followed by surgery and endocrine therapy. She developed left pleural metastases and is currently receiving targeted therapy. Internal mammary rhabdomyosarcomas are rare among PRSTSs and pose a diagnostic challenge for patients with breast cancer. Histological evaluation is important for the differential diagnosis of breast cancer relapses with secondary malignancies. The management of post-radiation thoracic rhabdomyosarcomas is challenging, and the prognosis is poor.